Citizens’ Spiritual Capital for Strengthening Character Development in Indonesian Civic Education - Chris Apandie; Silvia Rahmelia (JURNAL PENDIDIKAN, 2025)
This paper aims to explore the concept of citizens' spiritual capital as a theoretical foundation for character development within Indonesian Civic Education. Employing a systematic literature review methodology, the research synthesizes scholarly works to address three key questions: the role of spiritual capital as a theoretical base, its key dimensions, and strategies for its integration. The findings indicate that spiritual capital, defined as the inner resource of values, meaning, and life purpose, provides a crucial foundation for developing character. Four key dimensions were identified as relevant: values foundation, moral reasoning, social cohesion, and service orientation. The study concludes that effective integration requires a multi-level strategy, emphasizing a bottom-up approach starting from individual self-development, supported by the family, and reinforced through non-formal education and community practices. This approach is posited to be more effective in fostering ethically responsible citizens and achieving sustainable national character development than top-down models. The research offers insights for educators and policymakers in designing character education programs that holistically develop the spiritual, moral, and civic dimensions of learners. Keywords: Character Development, Civic Education, Indonesian Citizenship, Pancasila, Spiritual Capital